2023
DOI: 10.21203/rs.3.rs-2746877/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electronic Integrated Management of Childhood Illness (eIMCI): a randomized controlled trial to evaluate an electronic clinical decision-making support system for management of sick children in primary health care facilities in South Africa

Abstract: Background Electronic clinical decision-making support systems (eCDSS) aim to assist clinicians making complex patient management decisions and improve adherence to evidence-based guidelines. Integrated management of Childhood Illness (IMCI) provides guidelines for management of sick children attending primary health care clinics and is widely implemented globally. An electronic version of IMCI (eIMCI) was developed in South Africa. Methods We conducted a randomized controlled trial comparing management of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The overall proportion of IMCI symptoms and signs assessed at each individual consultation however remained low. The overall increase in the mean proportion of major IMCI symptom and signs assessed by health providers aligns with previous studies in Tanzania [13], Afghanistan [36], Nigeria [17], and Burkina Faso [16], but in contrast to findings in South Africa [15], that did not find improvements in the assessment of IMCI symptoms and signs. While these findings suggest that digital clinical decision support algorithms can positively enhance quality of care for sick children, there is much room for improvement.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall proportion of IMCI symptoms and signs assessed at each individual consultation however remained low. The overall increase in the mean proportion of major IMCI symptom and signs assessed by health providers aligns with previous studies in Tanzania [13], Afghanistan [36], Nigeria [17], and Burkina Faso [16], but in contrast to findings in South Africa [15], that did not find improvements in the assessment of IMCI symptoms and signs. While these findings suggest that digital clinical decision support algorithms can positively enhance quality of care for sick children, there is much room for improvement.…”
Section: Discussionsupporting
confidence: 88%
“…These tools, typically operating on electronic tablets or mobile phones, guide health providers through the consultation process, by prompting the evaluation of symptoms, signs, and recommended diagnostic tests, to finally propose the appropriate diagnosis and treatment [11,12]. While several studies have found that using these digital CDSAs improve adherence to IMCI, it is noteworthy that many of these investigations were conducted in controlled study settings, and most lacked randomization [13][14][15][16][17][18][19][20]. ePOCT+, a digital CDSA, was developed based on insights from two previous generations of CDSAs [21,22], specifically addressing challenges by our CDSAs and others, such as limited scope and information technology difficulties [23].…”
Section: Introductionmentioning
confidence: 99%